Single-crystal positive electrode material as well as preparation method and application thereof

By preparing single-crystal positive electrode materials through a three-step sintering method and additive optimization, the structural instability and interface side reaction problems of high-nickel, low-cobalt ternary positive electrode materials were solved, achieving excellent specific capacity and cycle performance.

CN120767306APending Publication Date: 2025-10-10GEM WUXI ENERGY MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510895764.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The high-nickel, low-cobalt ternary positive electrode material is structurally unstable under deep charging conditions, leading to side reactions and particle pulverization, affecting the specific capacity and cycle performance. In particular, in solid-state batteries, insufficient contact with the electrolyte leads to serious interfacial side reactions.

Method used

The single crystal positive electrode material is prepared by a three-step sintering method, which includes a primary sintering, a secondary sintering with the addition of a fast ion conductor and a water-soluble carbon source, and a third heating reaction to form a coating layer, combined with metal additives and inorganic active regulators to optimize the lithium content and crystal structure.

Benefits of technology

The specific capacity performance and cycle performance of single crystal positive electrode materials are improved, the interface side reactions are reduced, and the ion conduction rate and electron conduction capacity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005475950710000141
    Figure BDA0005475950710000141
  • Figure BDA0005475950710000151
    Figure BDA0005475950710000151
Patent Text Reader

Abstract

The invention belongs to the technical field of positive electrode materials, and particularly relates to a single-crystal positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: S1, mixing a ternary positive electrode material precursor and a first lithium source, and performing primary sintering to obtain a primary sintered material; s2, mixing the primary sintered material, a second lithium source and a fast ion conductor, and performing secondary sintering to obtain a secondary sintered material; s3, mixing the secondary sintering material, a water-soluble carbon source and water, heating for reaction, and performing third sintering to obtain a single crystal positive electrode material; the single-crystal positive electrode material disclosed by the invention has excellent specific capacity performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cathode materials, and in particular relates to a single crystal cathode material and a preparation method and application thereof. Background Art

[0002] High-nickel, low-cobalt ternary positive electrode materials (calculated as metal elements, the nickel content is greater than 80wt%, such as NCM811) have become one of the main development directions of ternary positive electrode materials due to their high theoretical specific capacity, and are currently one of the main development directions of solid-state battery positive electrode materials. However, when the nickel content in the positive electrode material is high, under deep charging conditions, structural instability is caused by anisotropic lattice contraction, local stress concentration occurs along the particle boundaries, and develops into microcracks, leading to serious side reactions and even particle pulverization. Studies have found that single-crystal positive electrode materials have many advantages that secondary spherical particles do not have, including: ① high mechanical strength, high compaction density, and not easy to crush; ② there is rarely any intergranular cracking caused by anisotropic expansion; ③ smooth surface and small interface side reactions.

[0003] However, the single crystal of the ternary cathode material also has its shortcomings. Due to the much larger primary grain size of the single crystal than the polycrystalline, the lithiation rate of the single crystal material during calcination is slower than that of the polycrystalline. In addition, the high content of nickel in the calcination process is 3+ Decomposition forms alkaline substances, resulting in residual alkali on the surface. Low residual alkali content leads to gelation of the positive electrode slurry, making coating difficult. It also combines with lithium, causing lithium deficiency on the surface of the material, significantly affecting the surface lattice stability, thereby affecting the specific capacity and cycle performance.

[0004] In addition, there are new challenges for solid-state battery positive electrode materials. The contact method and contact area between solid-state electrolytes and positive electrode materials are not as sufficient as those of liquid-phase batteries. In addition, existing solid-state electrolytes, especially sulfides, are prone to serious interfacial side reactions with positive electrode materials, causing electrolyte decomposition and gas generation, thereby affecting specific capacity and cycle performance. Summary of the Invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing positive electrode materials in that the specific capacity and cycle performance need to be improved, thereby providing a single crystal positive electrode material and its preparation method and application.

[0006] To this end, the present invention provides the following technical solutions:

[0007] A first aspect of the present invention provides a method for preparing a single crystal positive electrode material, wherein the method comprises the following steps:

[0008] S1, mixing a ternary cathode material precursor and a first lithium source, and performing a sintering operation to obtain a sintered material;

[0009] S2, mixing the first sintered material, the second lithium source, and the fast ion conductor, and performing secondary sintering to obtain the second sintered material;

[0010] S3, mixing the second sintered material, the water-soluble carbon source and water, heating for reaction, and performing three sintering to obtain a single crystal positive electrode material.

[0011] In the present invention, after the primary sintering, the method further comprises crushing, pulverizing and screening steps; after the secondary sintering, the method further comprises crushing and screening steps; after the tertiary sintering, the method further comprises screening steps.

[0012] According to the present invention, the molar ratio of the total metal elements in the ternary cathode material precursor to the lithium element in the first lithium source is 1:1-1.04.

[0013] According to the present invention, the molar ratio of the total metal elements in the ternary cathode material precursor to the lithium element in the second lithium source is 1:0.01-0.03.

[0014] In the present invention, the first lithium source and the second lithium source are conventional lithium sources in the art. Typically, but not limiting, the first lithium source and the second lithium source each independently include at least one of lithium hydroxide and lithium carbonate.

[0015] According to the present invention, the general formula of the ternary cathode material precursor is Ni a Co b Mn c (OH)2, wherein 0.80≤a<1.00, 0.05≤b<0.20, 0.01≤c<0.20, a+b+c=1.

[0016] According to the present invention, the average particle size of the ternary cathode material precursor is 2-5 μm.

[0017] According to the present invention, the fast ion conductor includes at least one of lithium aluminum titanium phosphate, tantalum fluoride, lithium niobate, lithium phosphate, and lithium tantalate.

[0018] According to the present invention, the fast ion conductor includes at least one of lithium aluminum titanium phosphate and lithium niobate.

[0019] According to the present invention, the mass percentage of the fast ion conductor is 0.2-1 wt % based on the mass of the ternary cathode material precursor.

[0020] According to the present invention, in step S1, a metal additive is also added during the mixing step.

[0021] According to the present invention, the metal additive includes metal oxides and / or metal hydroxides; optionally including at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, tantalum oxide, tungsten oxide, aluminum hydroxide, and magnesium hydroxide.

[0022] In the present invention, when there are multiple metal additives, the amounts of the multiple metal additives are supplemented according to actual needs, and there is no specific ratio relationship.

[0023] According to the present invention, the mass percentage of the metal additive is 0.5-1.5 wt % based on the mass of the ternary cathode material precursor.

[0024] According to the present invention, in step S2, an inorganic active regulator is also added during the mixing step.

[0025] According to the present invention, the mass percentage of the inorganic activity regulator is 0.5-1.5 wt % based on the mass of the ternary cathode material precursor.

[0026] According to the present invention, the inorganic activity regulator comprises a cobalt-containing compound and / or a phosphate.

[0027] In the present invention, when there are multiple inorganic activity regulators, the dosage of the multiple inorganic activity regulators is adjusted according to actual conditions, and there is no specific ratio relationship.

[0028] According to the present invention, the cobalt-containing compound includes at least one of cobaltous hydroxide, cobalt oxyhydroxide, and cobalt oxide.

[0029] In the present invention, the cobalt oxyhydroxide is CoO(OH), which has a birnessite-type layered structure, and the vertices of the octahedron are composed of oxygen ions (O 2- ) and hydroxide ions (OH - ) are jointly occupied; cobalt hydroxide is Co(OH)2, which is a brucite-type layered structure. Each cobalt ion (Co 2+ ) is located at the center of the octahedron, and the six vertices of the octahedron are occupied by six hydroxide ions (OH - ) occupies, each OH - Connect three Co 2+ ions, forming octahedral layers with shared vertices.

[0030] According to the present invention, the phosphate includes diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate.

[0031] According to the present invention, based on the mass of the second burnt material, the mass percentage of the water-soluble carbon source is 0.5-2wt%, and the mass percentage of the water is 40-80wt%.

[0032] According to the application, the water-soluble carbon source comprises at least one of glucose, citric acid, polyvinyl alcohol and sucrose, and optionally comprises glucose.

[0033] According to the application, in step S1, the temperature of the first sintering is 600-900℃, and the time is 6-20h, and optionally, the temperature of the first sintering is 700-800℃.

[0034] According to the application, in step S2, the temperature of the second sintering is 500-700℃, and the time is 4-10h.

[0035] According to the application, in step S3, the temperature of the heating reaction is 150-200℃, and the time is 20-60min.

[0036] In the application, in order to make the coating more uniform, the heating reaction is carried out in a pressure reaction tank in a closed manner, and the pressure is provided by water vapor generated by water heating. In order to mix more uniformly, the water-soluble carbon source and water can be mixed first, and then mixed with the second sintering material. After the heating reaction, a step of cooling to room temperature (20-25℃) and drying is further included. The drying conditions are conventional conditions in the art, and typically and non-limitingly, drying is carried out by drying, and the drying temperature is 80-150℃, and the time is not limited, and complete drying is sufficient.

[0037] According to the application, in step S3, the temperature of the third sintering is 400-600℃, and the time is 4-10h.

[0038] In the application, the first sintering and the second sintering are each independently sintered in an oxygen atmosphere. The third sintering is sintered in a protective gas due to the addition of the water-soluble carbon source in the step, and the gas atmosphere is nitrogen or inert gas, and the inert gas used is a conventional gas in the art, and typically and non-limitingly, includes argon and helium.

[0039] The second aspect of the application protects a single-crystal positive electrode material prepared by the above preparation method.

[0040] The third aspect of the application protects a secondary battery, wherein the secondary battery comprises the single-crystal positive electrode material described above.

[0041] The preparation method of the secondary battery is a conventional preparation method in the art.

[0042] The technical scheme of the application has the following advantages:

[0043] 1. The present invention provides a method for preparing a single crystal positive electrode material, wherein the preparation method comprises the following steps: S1, mixing a ternary positive electrode material precursor and a first lithium source, and performing a sintering process to obtain a first sintered material; S2, mixing the first sintered material, a second lithium source, and a fast ion conductor, and performing a second sintering process to obtain a second sintered material; S3, mixing the second sintered material, a water-soluble carbon source, and water, heating the mixture for reaction, and performing a third sintering process to obtain a single crystal positive electrode material; in the present invention, lithium sources are added to both step S1 and step S2 and sintered independently, which can effectively improve the ultra-high nickel The problems of slow lithiation of single crystals and high residual alkali content are solved; the coating layer prepared by adding a fast ion conductor in step S2 can greatly improve the ion conduction rate between the single crystal positive electrode material and the solid electrolyte; the coating layer prepared by adding a water-soluble carbon source in step S3 effectively isolates the positive electrode material and the solid electrolyte, thereby reducing interfacial side reactions; heating reaction can enable the water-soluble carbon source to construct a uniform pre-coating layer on the surface of the second-fired material, providing a basis for the third sintering; the above factors work together to make the single crystal positive electrode material of the present invention have excellent specific capacity performance, first-cycle efficiency and cycle performance.

[0044] 2. The specific type of fast ion conductor of the present invention can further improve the ion conduction rate, which is beneficial to the rapid migration of lithium ions; it can also further optimize the interface stability, so that the single crystal positive electrode material has excellent specific capacity performance and cycle performance.

[0045] 3. The specific type of water-soluble carbon source of the present invention can further promote the carbonization effect, improve the structural regularity of the coating layer prepared by the water-soluble carbon source, and provide better electron conduction ability.

[0046] 4. The addition of metal additives in the present invention can inhibit lattice distortion and stabilize the crystal structure; reduce surface residual alkali, inhibit side reactions, and enhance ion and electron conductivity, thereby further improving the electrical properties of the single crystal positive electrode material.

[0047] 5. The addition of an inorganic active regulator in the present invention can balance the lithium content, reduce activation energy, promote uniform grain growth, inhibit abnormal growth of single crystal particles, and further improve the specific capacity performance and cycle performance of the single crystal positive electrode material. DETAILED DESCRIPTION

[0048] The following examples are provided for a better understanding of the present invention and are not intended to limit the best mode of implementation. They do not limit the content and scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the scope of protection of the present invention.

[0049] The specific experimental steps or conditions are not indicated in the examples, and the operation or conditions can be carried out according to the conventional experimental steps described in the literature in the art. The reagents or instruments used are not indicated by the manufacturer, and are conventional reagent products that can be obtained on the market.

[0050] Cobalt oxyhydroxide, purchased from GREEM Co., Ltd.

[0051] Example 1

[0052] The present embodiment provides a single-crystal cathode material, and the preparation method comprises the following steps:

[0053] S1, 600g of Ni 0.92 Co 0.06 Mn 0.02 (OH)2 ternary cathode precursor, lithium hydroxide monohydrate, aluminum hydroxide, and zirconium oxide are mixed in a high-speed mixer, wherein the molar ratio of the sum of metal elements in the Ni 0.92 Co 0.06 Mn 0.02 (OH)2 ternary cathode precursor to lithium elements in lithium hydroxide monohydrate is 1:1.03, the mass percentage of aluminum hydroxide is 0.61wt% based on the mass of the ternary cathode material precursor, the mass percentage of zirconium oxide is 0.28wt%, and the mixture is placed in a muffle furnace for primary sintering at 800℃ for 10h in an oxygen atmosphere, and then crushed, pulverized, and sieved to obtain a primary sintered material;

[0054] S2, 600g of the primary sintered material obtained in step S1, lithium hydroxide, cobalt oxyhydroxide, and lithium niobate are mixed in a high-speed mixer, wherein the molar ratio of the sum of metal elements in the Ni 0.92 Co 0.06 Mn 0.02 (OH)2 ternary cathode precursor to lithium elements in lithium hydroxide is 1:0.02, the mass percentage of cobalt oxyhydroxide is 1wt% based on the mass of the ternary cathode material precursor, and the mass percentage of lithium niobate is 0.5wt%; the mixture is placed in a muffle furnace for secondary sintering at 600℃ for 6h in an oxygen atmosphere, and then pulverized and sieved to obtain a secondary sintered material;

[0055] S3, glucose and water are placed in a pressure reaction tank, stirred until completely dissolved, and then poured into 600g of the secondary sintered material obtained in step S2, wherein the mass percentage of glucose is 1wt% based on the mass of the secondary sintered material, and the mass percentage of water is 50wt%; the mixture is stirred and dispersed, and the pressure reaction tank is sealed. The pressure reaction tank is placed in an oven and heated at 180℃ for 40min, and then cooled to room temperature. The pressure reaction tank is opened, and the mixture is dried in an oven at 110℃ until completely dry to obtain a dried material. The dried material is placed in a muffle furnace for tertiary sintering at 500℃ for 6h in a nitrogen atmosphere, and then sieved to obtain a single-crystal cathode material.

[0056] Example 2

[0057] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0058] S1, 600g of Ni with an average particle size of 2μm 0.90 Co 0.08 Mn 0.02 (OH)2 ternary positive electrode precursor, lithium carbonate and titanium oxide are mixed in a high-speed mixer, wherein Ni 0.90 Co 0.08 Mn 0.02 The molar ratio of the total metal elements in the (OH)2 ternary positive electrode precursor to the lithium element in the lithium carbonate is 1:1.02. The mass percentage of titanium oxide used is 0.5wt% based on the mass of the ternary positive electrode material precursor. The product is placed in a muffle furnace and sintered at 600°C for 18h in an oxygen atmosphere. After crushing, pulverizing and sieving, a sintered material is obtained.

[0059] S2, 600g of the burnt material obtained in step S1, lithium carbonate, ammonium dihydrogen phosphate, and tantalum fluoride were mixed in a high-speed mixer, wherein Ni 0.90 Co 0.08 Mn 0.02 The molar ratio of the total metal elements in the (OH)2 ternary positive electrode precursor to the lithium element in the lithium carbonate is 1:0.01. Based on the mass of the ternary positive electrode material precursor, the mass percentage of ammonium dihydrogen phosphate is 1.2wt%, and the mass percentage of tantalum fluoride is 0.2wt%. The material is placed in a muffle furnace and sintered for a second time at 700°C in an oxygen atmosphere for 6h. The secondary sintered material is obtained by crushing and sieving.

[0060] In step S3, glucose and water are placed in a pressure reactor and stirred until completely dissolved. 600 g of the sintered material obtained in step S2 is then added, with the glucose and water being used in an amount of 2 wt % and 40 wt % of the sintered material, respectively. The mixture is stirred and dispersed, and the pressure reactor is sealed. The pressure reactor is placed in an oven and heated at 150° C. for 60 min. After cooling to room temperature, the pressure reactor is opened and the mixture is dried in an oven at 120° C. until completely dry to obtain a dried material. The dried material is placed in a muffle furnace and sintered three times at 600° C. for 4 h in a nitrogen atmosphere. The resulting single crystal cathode material is then sieved.

[0061] Example 3

[0062] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0063] S1, 600g of Ni with an average particle size of 5μm 0.88 Co 0.08 Mn0.04 (OH)2 ternary positive electrode precursor, lithium hydroxide monohydrate, magnesium oxide, aluminum oxide, and titanium oxide are mixed in a high-speed mixer, wherein Ni 0.88 Co 0.08 Mn 0.04 The molar ratio of the total metal elements in the (OH)2 ternary positive electrode precursor to the lithium element in the lithium hydroxide monohydrate is 1:1.01. Based on the mass of the ternary positive electrode material precursor, the mass percentage of magnesium oxide is 0.5wt%, the mass percentage of aluminum oxide is 0.5wt%, and the mass percentage of titanium oxide is 0.5wt%. The precursors are placed in a muffle furnace and sintered at 900°C for 8h in an oxygen atmosphere. After crushing, pulverizing, and sieving, a sintered material is obtained.

[0064] S2, 600g of the sintered material obtained in step S1, lithium hydroxide monohydrate, cobalt oxide, and lithium aluminum titanium phosphate were mixed in a high-speed mixer, wherein Ni 0.88 Co 0.08 Mn 0.04 The molar ratio of the total metal elements in the (OH)2 ternary positive electrode precursor to the lithium element in the lithium hydroxide monohydrate is 1:0.03. Based on the mass of the ternary positive electrode material precursor, the mass percentage of cobalt oxide is 0.5wt%, and the mass percentage of lithium aluminum titanium phosphate is 1wt%. The precursor is placed in a muffle furnace and subjected to secondary sintering at 500°C for 10h in an oxygen atmosphere. The secondary sintered material is obtained by crushing and sieving.

[0065] In step S3, glucose and water are placed in a pressure reactor and stirred until completely dissolved. 600 g of the sintered material obtained in step S2 is then added, with the glucose and water used in an amount of 0.5 wt% and 80 wt% of the sintered material, respectively, mixed and dispersed. The pressure reactor is then sealed. The pressure reactor is placed in an oven and heated at 200°C for 20 minutes. After cooling to room temperature, the pressure reactor is opened and the mixture is dried in an oven at 150°C until completely dry to obtain a dried material. The dried material is placed in a muffle furnace and sintered three times in a nitrogen atmosphere at 400°C for 10 hours. The resulting single crystal cathode material is then sieved.

[0066] Example 4

[0067] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0068] The method of Example 1 is the same as that of Example 1, except that in step S2, lithium niobate is replaced with lithium phosphate of the same mass.

[0069] Example 5

[0070] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0071] In the same manner as in Example 1, except that in step S3, glucose is replaced by an equal amount of citric acid.

[0072] Example 6

[0073] The present example provides a single-crystal cathode material, and a preparation method thereof includes the following steps:

[0074] In the same manner as in Example 1, except that in step S1, no metal oxidizing agent (aluminum hydroxide and zirconium oxide) is added.

[0075] Example 7

[0076] The present example provides a single-crystal cathode material, and a preparation method thereof includes the following steps:

[0077] In the same manner as in Example 1, except that in step S2, no inorganic activity modifier (cobalt hydroxide) is added.

[0078] Example 8

[0079] The present example provides a single-crystal cathode material, and a preparation method thereof includes the following steps:

[0080] In the same manner as in Example 1, except that in step S2, no inorganic activity modifier (cobalt hydroxide) is added.

[0081] Comparative Example 1

[0082] The present example provides a single-crystal cathode material, and a preparation method thereof includes the following steps:

[0083] In the same manner as in Example 2, except that in step S1, the molar ratio of the sum of metal elements in the ternary cathode precursor to lithium element in lithium carbonate is 1:1.03, and in step S2, no lithium carbonate is added.

[0084] Comparative Example 2

[0085] The present example provides a single-crystal cathode material, and a preparation method thereof includes the following steps:

[0086] In the same manner as in Example 8, except that in step S2, lithium niobate is replaced by an equal amount of aluminum oxide.

[0087] Comparative Example 3

[0088] The present example provides a single-crystal cathode material, and a preparation method thereof includes the following steps:

[0089] In the same manner as in Example 8, except that in step S3, glucose is replaced by an equal amount of aluminum oxide.

[0090] Comparative Example 4

[0091] This comparative example provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0092] S1, 600g of Ni with an average particle size of 3.5μm 0.92 Co 0.06 Mn 0.02 (OH)2 ternary positive electrode precursor, lithium hydroxide monohydrate, aluminum hydroxide, zirconium oxide, lithium hydroxide, cobalt oxyhydroxide, and lithium niobate are mixed in a high-speed mixer, wherein Ni 0.92 Co 0.06 Mn 0.02 The molar ratio of the total metal elements in the (OH)2 ternary positive electrode precursor to the lithium element in the lithium hydroxide monohydrate is 1:1.03. Based on the mass of the ternary positive electrode material precursor, the mass percentage of aluminum hydroxide is 0.61wt%, the mass percentage of zirconium oxide is 0.28wt%, and the mass percentage of Ni is 0. 0.92 Co 0.06 Mn 0.02 The molar ratio of the total metal elements in the (OH)2 ternary positive electrode precursor to the lithium element in the lithium hydroxide is 1:0.02. Based on the mass of the ternary positive electrode material precursor, the mass percentage of cobalt oxyhydroxide is 1wt%, and the mass percentage of lithium niobate is 0.5wt%. The precursor is placed in a muffle furnace and sintered at 800°C for 16 hours in an oxygen atmosphere. After crushing, pulverizing, and sieving, a sintered material is obtained.

[0093] In step S2, glucose and water are placed in a pressure reaction tank and stirred until completely dissolved. 600 g of the sintered material obtained in step S1 is then added. A quantity of glucose and water of the same mass as in Example 1 are added, and the mixture is stirred and dispersed. The pressure reaction tank is then sealed. The pressure reaction tank is placed in an oven and heated at 180°C for 40 minutes. After cooling to room temperature, the pressure reaction tank is opened and the mixture is dried in an oven at 110°C until completely dry to obtain a dried material. The dried material is placed in a muffle furnace and sintered three times at 500°C for 6 hours in a nitrogen atmosphere. The material is then sieved to obtain a single crystal positive electrode material.

[0094] Comparative Example 5

[0095] This comparative example provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0096] The method of Example 8 is the same, except that in step S3, glucose and water are placed in a pressure reaction tank and stirred until completely dissolved, and 600 g of the sintered material obtained in step S2 is poured into it. Based on the mass of the sintered material, the mass percentage of glucose is 1 wt %, and the mass percentage of water is 50 wt %. The mixture is stirred and dispersed to obtain a dried mixture, and then placed in a muffle furnace and sintered three times at 500° C. for 6 h in a nitrogen atmosphere. The single crystal positive electrode material is sieved.

[0097] Test Case

[0098] The single crystal positive electrode materials prepared in the examples and comparative examples were used to prepare lithium ion batteries. The specific method is as follows:

[0099] The positive electrode material: lithium phosphorus sulfur solid electrolyte: carbon fiber (VGC): polytetrafluoroethylene (PTFE) mass ratio is 60:30:5:5, centrifuged and mixed evenly to obtain a positive electrode mixture, which was dry-rolled into a film and punched into a positive electrode sheet with a diameter of 10 mm. The positive electrode material coating surface density is 30 mg / cm 2 . 60mg of lithium phosphorus sulfur chlorine solid electrolyte was pressed into shape at a pressure of 4t to obtain a solid electrolyte membrane layer. The positive electrode sheet was placed on the solid electrolyte membrane layer and pressed at a pressure of 4t for 5 minutes to form a composite positive electrode material and a solid electrolyte membrane layer. First, a current collector (aluminum foil) was added to the solid-state battery fixture, followed by the composite positive electrode material and the solid electrolyte membrane layer, and finally the lithium indium negative electrode was placed. After assembly, it was pressed at a pressure of 2t for 5 minutes to form a mold solid-state battery, which was then tested.

[0100] First cycle charge capacity and first cycle discharge capacity: At 25°C, charge to 4.25V at a rate of 0.2C, and then discharge to 2.80V at a rate of 0.2C. This is a cycle process to obtain the charge / discharge capacity. First charge capacity = first charge capacity / battery mass, first discharge capacity = first discharge capacity / battery mass;

[0101] First cycle efficiency: First cycle efficiency = first discharge capacity / first charge capacity × 100%;

[0102] 1C specific capacity: After 2 cycles, charge at a rate of 0.5C to 4.25V, then discharge at a rate of 1C to 2.80V. Record the discharge capacity at the third cycle. 1C discharge specific capacity = 1C discharge capacity / battery mass.

[0103] Cycle retention rate: After 2 cycles, charge at a rate of 0.5C to 4.25V, then discharge at a rate of 1C to 2.80V, cycle 50 times, record the discharge capacity at the 3rd cycle, and record the discharge capacity at the 52nd cycle. Cycle retention rate = discharge capacity at the 52nd cycle / discharge capacity at the 3rd cycle × 100%;

[0104] The test results are shown in Table 1;

[0105] Table 1

[0106]

[0107]

[0108] It can be seen from the data in Table 1 that, compared with the comparative example, the embodiment has better specific capacity performance and cycle performance.

[0109] A comparison between Example 1 and Example 4 shows that the specific type of fast ion conductor of the present invention can further improve the ion conduction rate, which is beneficial to the rapid migration of lithium ions; it can also further optimize the interface stability, so that the single crystal positive electrode material has excellent specific capacity performance and cycle performance.

[0110] Comparison between Example 1 and Example 5 shows that the specific type of water-soluble carbon source of the present invention can further promote the carbonization effect, improve the structural regularity of the coating layer prepared by the water-soluble carbon source, and have better electron conduction ability.

[0111] Comparison between Example 1 and Example 6 shows that the addition of metal additives can inhibit lattice distortion and stabilize the crystal structure; reduce surface residual alkali, inhibit side reactions, and enhance ion and electron conductivity, thereby further improving the electrical properties of the single crystal positive electrode material.

[0112] Comparison between Example 1 and Example 7 shows that the addition of an inorganic active regulator can balance the lithium content, reduce the sintering activation energy, promote uniform grain growth, inhibit the abnormal growth of single crystal particles, and further improve the specific capacity performance and cycle performance of the single crystal positive electrode material.

[0113] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will appreciate that other variations or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A method for preparing a single crystal positive electrode material, characterized in that: The preparation method comprises the following steps: S1, mixing a ternary cathode material precursor and a first lithium source, and performing a sintering operation to obtain a sintered material; S2, mixing the first sintered material, the second lithium source, and the fast ion conductor, and performing secondary sintering to obtain the second sintered material; S3, mixing the second sintered material, the water-soluble carbon source and water, heating for reaction, and performing three sintering to obtain a single crystal positive electrode material.

2. The preparation method according to claim 1, characterized in that The general formula of the ternary cathode material precursor is Ni a Co b Mn c (OH)2, wherein 0.80≤a<1.00, 0.05≤b<0.20, 0.01≤c<0.20, a+b+c=1; And / or, the average particle size of the ternary cathode material precursor is 2-5 μm.

3. The preparation method according to claim 1 or 2, characterized in that The fast ion conductor includes at least one of lithium aluminum titanium phosphate, tantalum fluoride, lithium niobate, lithium phosphate, and lithium tantalate; Optionally, the fast ion conductor includes at least one of lithium aluminum titanium phosphate and lithium niobate; And / or, based on the mass of the ternary cathode material precursor, the mass percentage of the fast ion conductor is 0.2-1 wt%.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step S1, a metal additive is also added during the mixing step; Optionally, the metal additive includes metal oxides and / or metal hydroxides; optionally including at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, tantalum oxide, tungsten oxide, aluminum hydroxide, and magnesium hydroxide; Optionally, based on the mass of the ternary cathode material precursor, the mass percentage of the metal additive is 0.5-1.5 wt%.

5. The preparation method according to any one of claims 1 to 4, characterized in that In step S2, an inorganic active modifier is also added during the mixing step; Optionally, the mass percentage of the inorganic active regulator is 0.5-1.5 wt % based on the mass of the ternary cathode material precursor; Optionally, the inorganic active modifier comprises a cobalt-containing compound and / or a phosphate; Optionally, the cobalt-containing compound includes at least one of cobaltous hydroxide, cobalt oxyhydroxide, and cobalt oxide; Optionally, the phosphate includes diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate.

6. The preparation method according to any one of claims 1 to 5, characterized in that Based on the mass of the second burnt material, the mass percentage of the water-soluble carbon source is 0.5-2wt%, and the mass percentage of the water is 40-80wt%; Optionally, the water-soluble carbon source includes at least one of glucose, citric acid, polyvinyl alcohol, and sucrose.

7. The preparation method according to any one of claims 1 to 6, characterized in that In step S1, the primary sintering temperature is 600-900°C and the time is 6-20 hours; optionally, the primary sintering temperature is 700-800°C; And / or, in step S2, the secondary sintering temperature is 500-700°C and the time is 4-10 hours; And / or, in step S3, the heating reaction temperature is 150-200° C. and the time is 20-60 min; And / or, in step S3, the temperature of the three sinterings is 400-600° C., and the time is 4-10 hours.

8. The preparation method according to claim 7, characterized in that The molar ratio of the total metal elements in the ternary cathode material precursor to the lithium element in the first lithium source is 1:1-1.04; The molar ratio of the total metal elements in the ternary cathode material precursor to the lithium element in the second lithium source is 1:0.01-0.

03.

9. A single crystal positive electrode material obtained by the preparation method according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the single crystal positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of carbon-coated single-crystal lithium nickel cobalt manganate ternary positive electrode material

    CN111172582A

  • Monocrystal ternary positive electrode material, preparation method thereof and lithium ion battery

    CN115676911A

  • Ternary positive electrode material coated with fast ion conductor, preparation method and lithium ion battery

    CN118412456A

  • High-nickel single-crystal positive electrode material as well as preparation method and application thereof

    CN119890302A